Does Smartphone-Based Quizlet Affect Students Learning Interest? - Styaningrum, Farida; Sulistyowati, Nur Wahyuning; Wibowo, Agus (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aimed to provide empirical evidence of the effect of smartphone-based Quizlet on students’ learning interest in Universitas PGRI Madiun, Indonesia. This study was pre-experimental with a one-shot case study that is a group that got help, and the results were observed next. The population were accounting education students in Universitas PGRI Madiun. 54 students received smartphone-based Quizlet assistance in learning activities. We used statistical testing to test comparisons formulated in research hypotheses using simple linear regression tests. The results proved empirically that the use of smartphone-based Quizlet affected the students' learning interest in Universitas PGRI Madiun, Indonesia. The menu provided in the Quizlet application could activate students in learning and give a positive effect to students. Students became active in learning activities, did assignments on time, and learnt independently. The Quizlet application can be used as material for educators to consider increasing student interest in learning social science.